Land Reform in Nepal: Concepts, Models, Policies and Implementation - Dahal, Lila Nath (Tri-Chandra Journal of Anthropology, 2025)
Land reform in Nepal remains a complex and pressing issue, deeply intertwined with political, social, and economic factors. Initially implemented through the Lands Act of 1964, land reform aimed to ensure equitable land distribution, protect tenant rights, and promote agricultural productivity. Despite its ambitious goals, the implementation has been inconsistent, with significant gaps between policy, law, and practice. This study uses a mixed-methods approach, combining household surveys and interviews with secondary data, to analyze land ownership patterns and the relationship between landholderss and tenants in Changunarayan Municipality, Bhaktapur. Key challenges include ineffective enforcement of land ceilings, unresolved dual ownership conflicts, and limited success in increasing agricultural productivity. Political manipulation and lack of coordination among stakeholders have further undermined reform efforts, often reducing land reform to a political slogan rather than a developmental initiative. Recent policies, such as the National Land Policy, 2075 B.S. and Land Use Act, 2076 B.S., emphasize sustainable land management and socio-economic inclusivity, but their success depends on harmonized legal frameworks and effective implementation. Nepal must address underlying structural issues, balance ownership with productivity, and align reform efforts with broader economic and social goals to achieve meaningful outcomes.